Mental health reform under policy mainstreaming: needed, but uncertain. (March 2014) - Hogan, M.
<x content-type="archive" xml:space="preserve">Abstract</x> October 2013 marks the 50th anniversary of President John F. Kennedy's message to the US Congress on the need to reform mental healthcare. Much has changed in that time. In 2006, Frank and Glied summarized these changes and the forces behind them, finding that the well-being of people with mental illness was 'better but not well.' They also conclude that most improvements have been due to 'mainstreaming, ' the inclusion of those with mental illness in broad reforms such as Medicare, Medicaid and Social Security. With the gradual assimilation of mental health concerns, leadership and resources into mainstream programmes and agencies, future improvements will require that these programmes are accessible and oriented to people with mental illness. The passage of broad health reform legislation in 2010 (the Affordable Care Act) reinforces this change; several of its provisions attempt to make healthcare more relevant to the population with mental illness. In this editorial, I discuss a set of challenges which remain for the population with mental illness in the healthcare system, and the prospects for change. These challenges include: (1) improving basic mental healthcare in primary care, (2) improving mental healthcare for children, (3) earlier detection and treatment of psychotic illness, (4) disability and unemployment and (5) the challenge of sustaining an adequate, speciality public mental healthcare system under conditions of mainstreaming. In general, I conclude that the prospects for successful reform are uncertain. Establishing mental healthcare specialization in mainstream systems has not been notably successful to date.